A cleaning process for the removal and stabilisation of arsenic from arsenic-rich lead anode slime. (1st March 2018) - Chen, Yongming; Liu, Nannan; Ye, Longgang; Xiong, Shan; Yang, Shenghai
Abstract: A cleaning process, including the steps of alkaline leaching, precipitation of lead and stabilization of arsenic, was proposed for separation of arsenic from lead anode slime generated in lead smelter before valuable metals recycling. The anode slime was first leached by NaOH solution at oxygen pressure, and the optimum conditions were obtained as follows: α (NaOH) = 1.2 (where α represents excess coefficient), temperature 160 °C, liquid-solid ratio 5:1, oxygen partial pressure 1.2 MPa, where the leaching rates of arsenic and lead reached 95.65% and 0.96%. Second, the leaching solution underwent oxidative precipitation for lead separation in the form of PbO2 using sodium persulfate as oxidizing agent. Under the optimum conditions, the precipitation rate of lead was 94.53%. Then, the sodium arsenate was crystallized from the latter precipitation solution. Finally, the re-dissolving arsenic was solidified by the atmospheric oxidation method to form scorodite crystal. A suitable pH range for scorodite formation was below pH 6.0, where the highest precipitation rate of As was 88.48%. However, for solution pH higher than 6.0, the precipitates were very fine and showed inferior crystallinity as well as being unsafe for long-term stockpiling. It is suggest that this process has potential application for dearsenification from all arsenic-rich anode slime. Graphical abstract: The schematic diagram of As stabilization mechanism. Image 1 Highlights: A cleaning process was proposed for separation and stabilization of arsenic. The leaching rate of arsenic reached 95.65% in selectivity leaching process. Oxidative precipitation was used to recover lead from alkaline leaching solution. It is feasible to synthesize scorodite in wide pH range by atmospheric oxidation.